2006
DOI: 10.1158/1078-0432.ccr-05-2363
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gains on 1q and Epidermal Growth Factor Receptor Overexpression as Independent Prognostic Markers in Intracranial Ependymoma

Abstract: Purpose: Pathogenesis of ependymomas is still poorly understood and molecular markers for risk-adapted patient stratification are not available. Our aim was to screen for novel genomic imbalances and prognostic markers in ependymal tumors. Experimental Design: We analyzed 68 sporadic tumors by matrix-based comparative genomic hybridization using DNA microarrays containing >6,400 genomic DNA fragments. Novel recurrent genomic gains were validated by fluorescence in situ hybridization using a tissue microarray c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
192
3
10

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(221 citation statements)
references
References 49 publications
16
192
3
10
Order By: Relevance
“…Consistent with this, an increase in DNA copy number of the physical location of human YVH1 at 1q, 5 has been observed in numerous cancers, including retinoblastoma, 30 liposarcomas 31 and intracranial ependymoma. 32 Importantly, hYVH1 was proposed to be oncogenic in the latter subset of cancers. 32 The mechanism by which hYVH1 affects cellular DNA content is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, an increase in DNA copy number of the physical location of human YVH1 at 1q, 5 has been observed in numerous cancers, including retinoblastoma, 30 liposarcomas 31 and intracranial ependymoma. 32 Importantly, hYVH1 was proposed to be oncogenic in the latter subset of cancers. 32 The mechanism by which hYVH1 affects cellular DNA content is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…32 Importantly, hYVH1 was proposed to be oncogenic in the latter subset of cancers. 32 The mechanism by which hYVH1 affects cellular DNA content is still unclear. The increased DNA content (4N and polyploidy) in asynchronous populations and nocodazole-treated U2OS cells suggest a failure of cytokinesis, although uncontrolled DNA replication cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PDGF receptors, 14,30 reports of c-Abl expression in central nervous system tumors remain sparse. It has been demonstrated that tyrosine kinases play a functional role in a variety of pediatric neoplasms, [11][12][13][14][15] and the few studies that have evaluated c-Abl expression in brain tumors encountered low expression levels in only a fraction of tumors. For example, Haberler et al observed focal c-Abl expression in only 7 of 101 glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data suggest that tyrosine kinase receptor signaling may play a role in the biology of more common pediatric solid tumors, such as medulloblastomas, ependymomas, and choroid plexus tumors, and in Ewing sarcomas and neuroblastomas. [9][10][11][12][13][14][15][16] Imatinib, a tyrosine kinase inhibitor directed against c-Abl, c-Kit and platelet-derived growth factor (PDGF) receptor subtypes a and b, 17 reportedly is tolerated relatively well in children. 18,19 Because it has been demonstrated that imatinib inhibits proliferation of the rhabdoid tumor cell line BT12, 20 our objective was to investigate the expression and functional role of tyrosine kinases targeted by imatinib in rhabdoid tumors.…”
mentioning
confidence: 99%
“…This is supported by studies of CDKN2A (p14ARF), a tumor suppressor gene located at 9p21.3 that regulates neural stem cell proliferation and whose deletion has been shown to rapidly expand progenitor cell numbers in developing neural tissue (33,34). Whereas gene expression analysis has revealed that CDKN2A is upregulated in spinal tumors (77,86), it is downregulated by a much stronger magnitude in intracranial tumors (86). Furthermore, while epigenetic analysis has shown a significant difference in the methylation status of neighboring CDKN2B between spinal and intracranial tumors (79), fluorescent in situ hybridization (FISH) has shown that CDKN2A deletion is virtually exclusive to supratentorial ependymomas (34).…”
Section: Ependymoma Heterogeneity and Tumor Locationmentioning
confidence: 91%